Coronary plaque progression is greater in systemic lupus erythematosus than rheumatoid arthritis. Issue 1 (24th November 2022) - Moore, Jeff; Lakshmanan, Suvasini; Manubolu, Venkat Sanjay; Kinninger, April; Stojan, George; Goldman, Daniel W.; Petri, Michelle; Budoff, Matthew; Karpouzas, George A.
Abstract : Background: Systemic lupus erythematosus (SLE) and rheumatoid arthritis (RA) are associated with a high incidence of cardiovascular disease. Coronary atherosclerosis, particularly total plaque and noncalcified plaque on coronary computed tomography angiography (CCTA) has been correlated with cardiovascular events. We compared baseline coronary plaque burden and progression by serial CCTA in SLE and RA patients. Methods: We prospectively evaluated 44 patients who underwent serial CCTA examinations to quantify coronary plaque progression, 22 SLE patients, and 22 age- and sex-matched RA patients. Semiautomated plaque software was used for quantitative plaque assessment. Linear regression examined the effect of SLE diagnosis (versus RA) on annualized change in natural log-transformed total normalized atheroma volume (ln-TAVnorm ) for low-attenuation, fibrofatty, fibrous, total noncalcified, densely calcified, and total plaque. Results: No quantitative differences for any plaque types were observed at baseline between SLE and RA patients ( P = 0.330–0.990). After adjustment for baseline plaque and cardiovascular risk factors, the increase in ln-TAVnorm was higher in SLE than RA patients for fibrous [Exp-β: 0.202 (0.398), P = 0.0003], total noncalcified [Exp-β: 0.179 (0.393), P = 0.0001], and total plaque volume [Exp-β: 0.154 (0.501), P = 0.0007], but not for low-attenuation, fibrofatty, or densely calcified plaque ( P = 0.103–0.489). Patients with SLE had 80% more fibrous, 82% more noncalcified, and 85% more total plaque increase than those with RA. Conclusion: Coronary plaque volume was similar in RA and SLE at baseline. Progression was greater in SLE, which may explain the greater cardiovascular risk in this disease. Further research to evaluate screening and management strategies for cardiovascular disease in these high-risk patients is warranted.